Peningkatan Hasil Belajar PAI Menggunakan PBL di Kelas VII.2 UPTD SMPN 3 Kec. Pangkalan Koto Baru - Selvi Yanti; Syawaluddin Syawaluddin; Deslita Deslita; Nur Arifah; Nurhasanah Nurhasanah; Azimatul Husna (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low ability to read the Al-Qur'an in class VII.2 students at UPTD SMP Negeri 3 Pangkalan Koto Baru District. This research aims to improve the Al-Quran reading ability of class VII.2 students at UPTD SMP Negeri 3 Pangkalan Koto Baru District through the Problem Based Learning method. The type of research used is Classroom Action Research (PTK) with the Problem Based Learning (PBL) model. The method used in the research is two cycles, namely the Problem Based Learning method. Each cycle consists of 4 stages, namely planning, implementation/action, observation/observation, and reflection. Each cycle consists of one meeting (3 lesson hours). The population used was 28 people. The data collection techniques used were observation, tests and interviews. The results of this research show an increase in students' ability to read the Al-Quran from pre-action, cycle I and cycle II. The learning outcomes of students who completed at the pre-action stage were 5 students or 30%, in cycle I (first) the value of students who completed increased by 11 people or 69%, in cycle II (second) it increased again with the number of students 15 people or 94% completed. Thus, a recommendation can be put forward that the application of the Problem Based Learning method in learning can improve student PAI learning outcomes in VII.2 at UPTD SMP Negeri 3 Pangkalan Koto Baru District.